HUBUNGAN MOTIVASI DAN PENGETAHUAN RELAWAN TERHADAP PENANGGULANGAN BENCANA BANJIR DI KABUPATEN GRESIK - Vita Arum Dani; Mohammad F. N. Aulady; Diah Listyaningsih (Republic of Indonesia Defense University, 2023)
Flood is a disaster caused by water discharge increase resulting in submerging the surrounding area. Gresik is a regency that often experiences floods. Volunteers are involved in flood prevention. Effective and efficient disaster management requires volunteers who rely not only on skills and willingness but also on motivation and knowledge. This research investigated the correlation between the motivation to be a volunteer and knowledge of flood disaster management. This research was conducted by distributing questionnaires to 59 volunteers who met the inclusion criteria. The results of the data analysis obtained Pearson Correlation (Product Moment) having a significance value of 0.000 or less than 0.05. The Pearson Correlation value of 0.791 indicated that the correlation between motivation (X) and flood disaster knowledge in Gresik Regency (Y) was positive (good) and strong. The results of the Simple Linear Regression Test obtained Y = 7.260 + 0.856X + ei, while the T-test motivation variable (X) showed a significant number of 0.000 or less than 0.05 (Sig. <0.05) and t-count (9.773) > t-table (2.00324). Since H0 was rejected, whereas Ha was accepted, the provisional assumption (hypothesis) was correct. In other words, there was a correlation between Motivation (X) and Knowledge of Flood Disasters in Gresik Regency (Y).